Atomistic study of dynamics for metallic filament growth in conductive-bridge random access memory. Issue 14 (14th April 2015) - Qin, Shengjun; Liu, Zhan; Zhang, Guo; Zhang, Jinyu; Sun, Yaping; Wu, Huaqiang; Qian, He; Yu, Zhiping
<x xml:space="preserve">Abstract</x> The growth dynamics for metallic filaments in conductive-bridge resistive-switching random access memory (CBRAM) are studied using the kinetic Monte Carlo (KMC) method.